HAIR TONIC SHAMPOO FORMULATION WITH AMBON BANANA (MUSA ACUMINATA COLLA) CORM EXTRACT - INDRAWATI, TETI; SIMANJUNTAK, LASTIAR; PRATAMI, DIAH KARTIKA (International Journal of Applied Pharmaceutics, 2020)
Objective: Banana waste, especially corms, has potential as a source of haircare agents due to its active compound, anthraquinone, which is known to promote hair growth. This study aimed to assess preparations of hair tonic shampoo containing Musa acuminata Colla corm extract and evaluate their characteristics and stability. Methods: Three shampoo formulas were prepared containing 8%, 10%, and 12% corm extract. Physical stability tests were performed at high (60±2 °C) and room temperature (25±2 °C) for three weeks. The shampoo formulas were evaluated for their organoleptic properties (colour, form, and odour), homogeneity, pH, density, viscosity, rheology, foam height and stability, and surface tension. Results: The shampoo formulas with corm extract were white to yellowish-white, creamy, and smelled of banana, and were homogenous without precipitation. The formulas had a pH of 6.08–6.12, a density of 1.027–1.054 g/ml, foam height of 3.56–3.63 ml, the surface tension of 28.92–29.85 dyne/cm, viscosity of 16,000–120,000 cps and pseudoplastic flow properties. Conclusion: The natural hair tonic shampoo formulas prepared with M. acuminata corm have good characteristics.